Resistance [videorecording (DVD)] - Jakubowicz, Jonathan, 1978-; Jakubowicz, Jonathan, 1978-; Eisenberg, Jesse, 1983-; Harris, Ed, 1950-; Poésy, Clémence (Shout! Factory, 2020)
Follows aspiring mime artist Marcel Marceau as he joins the French Resistance during World War II to help save thousands of orphaned Jewish children.